Design, synthesis and biological evaluation of novel thiazol-2-yl benzamide derivatives as glucokinase activators. (April 2018) - Charaya, Neha; Pandita, Deepti; Grewal, Ajmer Singh; Lather, Viney
Graphical abstract: Highlights: Novel thiazol-2-yl benzamide derivatives were designed and synthesized as allosteric GK activators. The in vitro evaluation of the synthesized molecules displayed their potential GK activation activity. Docking study of the designed molecules revealed their binding interactions in the allosteric site of GK. Amongst the synthesized molecules, compounds 2 and 8 exhibited highest antidiabetic activity in OGTT. Abstract: Glucokinase (GK) is the main enzyme which controls the blood glucose levels in a safe and narrow physiological range in humans. GK activators are the novel type of therapeutic agents which act on GK enzyme and show their anti-diabetic potential. The present work was planned to synthesize and evaluate the antidiabetic potential of a new series of thiazole-2-yl benzamide derivatives as potential GK activators. A series of thiazole-2-yl benzamide derivatives were synthesized from benzoic acid and evaluated by in vitro enzymatic assay for GK activation. In silico docking studies were carried out to determine the binding interactions for the best fit conformations in the allosteric site of GK enzyme. Based on the results of in vitro enzyme assay and in silico studies, the selected molecules were tested for their antidiabetic activity in the oral glucose tolerance test (OGTT). The results of the in vitro enzymatic assay were found to be in accordance to that of in silico studies. Amongst the synthesized molecules, compounds 1, 2, 5 and 8 displayed good in vitro GK activation (activation fold between 1.48 and 1.83). Compounds 2 and 8 exhibited highest antidiabetic activity in OGTT studies. The results of the in vivo antidiabetic studies were found to be in parallel to that of docking and in vitro studies. These newly synthesized thiazol-2-yl benzamide derivatives thus can be treated as the initial hits for the development of new, safe, effective and orally bioavailable GK activators as therapeutic agents for the treatment of type 2 diabetes.